DOP041 Surgery and hospitalisation in patients with inflammatory bowel disease; 10-year follow-up of a Danish population-based inception cohort. (16th January 2018) - Lo, B; Vind, I; Bendtsen, F; Vester-Andersen, M; Burisch, J
Abstract: Background: The long-term disease course of Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), in the age of biologics has not been well described. We aimed to characterise the disease course after 10 years in CD and UC patients in a well-defined population based inception cohort. Methods: All patients ( n = 513) diagnosed with CD, UC or IBD unclassified between January 1, 2003 and December 31, 2004 in a well-defined Copenhagen area were included. Clinical data regarding treatment and outcome were recorded and patient records linked with four national registries to ensure complete data capture and follow-up. Major surgery was defined as any colectomy or intestinal resection. Disease classification was made according to the Montreal Classification. Hospitalisation was defined as any hospitalisation 3 months after date of diagnosis. Treatment with immunomodulators and biologics prior to the surgery was included in a regression model. Results: A total of 213 CD and 300 UC were followed for a mean of 9.24 years (sd: 2.68). In CD, during follow-up 75 (35%) patients underwent at least one major surgery, while 196 (92%) were hospitalised at least once. The median length of stay (LOS) was 3 days (IQR: 1–8) and the median number of hospitalisation was 7 (IQR: 4–13). In UC, 35 (12%) patients had a colectomy and 258 (86%) were hospitalised. The median LOS was 3 days (IQR: 1–8) and median number of hospitalisations was 5 (IQR: 3–8). Cumulative risk of major surgery and associated factors are show in Table 1 and Figures 1 and 2. Conclusions: In the age of biologics, the risk of resection and hospitalisation remains high for CD as well as for UC. The use of immunomodulators but not biologics was associated with a reduced risk of surgery in CD.